Performance of missing transverse momentum reconstruction with the ATLAS detector using proton-proton collisions at s = 13 TeV - Aaboud, M; Aad, G; Abbott, B; Abdinov, O; Abeloos, B; Abidi, S H; AbouZeid, O S; Abraham, N L; Abramowicz, H; Abreu, H; Abreu, R; Abulaiti, Y; et al. (The European physical journal. C, Particles and fields, 2018)
The performance of the missing transverse momentum ( E T miss ) reconstruction with the ATLAS detector is evaluated using data collected in proton-proton collisions at the LHC at a centre-of-mass energy of 13 TeV in 2015. To reconstruct E T miss , fully calibrated electrons, muons, photons, hadronically decaying τ -leptons , and jets reconstructed from calorimeter energy deposits and charged-particle tracks are used. These are combined with the soft hadronic activity measured by reconstructed charged-particle tracks not associated with the hard objects. Possible double counting of contributions from reconstructed charged-particle tracks from the inner detector, energy deposits in the calorimeter, and reconstructed muons from the muon spectrometer is avoided by applying a signal ambiguity resolution procedure which rejects already used signals when combining the various E T miss contributions. The individual terms as well as the overall reconstructed E T miss are evaluated with various performance metrics for scale (linearity), resolution, and sensitivity to the data-taking conditions. The method developed to determine the systematic uncertainties of the E T miss scale and resolution is discussed. Results are shown based on the full 2015 data sample corresponding to an integrated luminosity of 3.2 fb - 1 .